The meaning of a bad childbirth experience: A qualitative study with women in Rwanda - Berg, Marie (University of Gothenburg, 2017)
Objective
Being pregnant and giving birth is a pivotal life event and one that a woman ordinarily remembers for most of her life. A negative childbirth experience can affect a woman’s health well beyond the episode of the labour and birth itself. This study explored the meaning of a bad childbirth as experienced by women who have given birth in Rwanda.
Methods
In a cross-sectional household study conducted in Northern Province and in Kigali City, the capital of Rwanda, a structured questionnaire was answered by women who had given birth 1 to 13 months earlier. One question answered by 898 women asked them to rate their overall experience of childbirth from 0 (very bad) to 10 (very good). Of these, 28 women (3.1%) rating the childbirth experience as bad (< 4) were contacted for individual interviews. Seventeen of these women accepted to participate in individual in-depth interviews. The texts were analysed with a reflective lifeworld approach.
Results
The essential meaning of a “bad” childbirth experience was that the women had been exposed to disrespectful care, constituted by neglect, verbal or physical abuse, insufficient information, and denial of their husband as a companion. The actions of carers included abandonment, humiliation, shaming and insult, creating feelings of insecurity, fear and distrust in the women. Two of the women reported no bad experience of care; their low rating was related to having suffered from medical complications.
Conclusion
It is challenging that the main finding is that women are exposed to disrespectful care. In efforts to provide a quality and equitable maternal health care system in Rwanda, there is need to focus on activities to implement respectful, evidence-based care for all. One such activity is to develop and provide education programmes for midwives and nurses about professional behaviour when caring for and working with women during labour and birth.
Purpose:
The aim of the study is to explore the meaning of a bad childbirth as experienced by women who had given birth in Rwanda.

Objective
Being pregnant and giving birth is a pivotal life event and one that a woman ordinarily remembers for most of her life. A negative childbirth experience can affect a woman’s health well beyond the episode of the labour and birth itself. This study explored the meaning of a bad childbirth as experienced by women who have given birth in Rwanda.
Methods
In a cross-sectional household study conducted in Northern Province and in Kigali City, the capital of Rwanda, a structured questionnaire was answered by women who had given birth 1 to 13 months earlier. One question answered by 898 women asked them to rate their overall experience of childbirth from 0 (very bad) to 10 (very good). Of these, 28 women (3.1%) rating the childbirth experience as bad (< 4) were contacted for individual interviews. Seventeen of these women accepted to participate in individual in-depth interviews. The texts were analysed with a reflective lifeworld approach.
Results
The essential meaning of a “bad” childbirth experience was that the women had been exposed to disrespectful care, constituted by neglect, verbal or physical abuse, insufficient information, and denial of their husband as a companion. The actions of carers included abandonment, humiliation, shaming and insult, creating feelings of insecurity, fear and distrust in the women. Two of the women reported no bad experience of care; their low rating was related to having suffered from medical complications.
Conclusion
It is challenging that the main finding is that women are exposed to disrespectful care. In efforts to provide a quality and equitable maternal health care system in Rwanda, there is need to focus on activities to implement respectful, evidence-based care for all. One such activity is to develop and provide education programmes for midwives and nurses about professional behaviour when caring for and working with women during labour and birth.
Syfte:
The aim of the study is to explore the meaning of a bad childbirth as experienced by women who had given birth in Rwanda.
The meaning of a bad childbirth experience
Keywords: childbirth; barnafödsel; Medical and Health Sciences; Medicin och hälsovetenskap